(untitled) (Quinto Sol, 2022)
This article proposes a comparative analysis of the different constitutional reforms in the province of Corrientes of 1889, 1913 and 1949 with the purpose of enquiring about representations regarding laicism, religion and state that are shown in those. Its main focus is to study the debates that were raised in the conventions, to identify the different stances by political parties and ideologies, the actors involved, the arguments in each case around the matter and other regarding those, such as religious education. From that analysis we are looking to contribute to the knowledge regarding the process of laicism in Argentina from the perspective of a province case.